A quality assessment of clinical practice guidelines with recommendations for family involvement in the care of individuals diagnosed with schizophrenia, bipolar mood disorder, and major depressive disorder: Critical appraisal utilizing AGREE II - Dehbozorgi, Raziye; Fereidooni-Moghadam, Malek; Shahriari, Mohsen; Moghimi-Sarani, Ebrahim (Frontiers in Psychiatry, 2023)
Introduction: Evidence suggests that family-center collaborative care is useful for individuals identified with chronic mental illness. Clinical practice guidelines offer specific recommendations primarily based on to be had studies and are beneficial in informing evidence-based practice and guiding destiny studies. Objective: Identify current scientific practice guidelines including family-center collaborative care suggestions for individuals with Schizophrenia, Bipolar Mood Disorder, and Major Depressive Disorder and critically appraise the methodological quality of the selected guidelines. Methods: A systematic search was performed on seven electronic databases (G-I-N), (NICE), (MOH), (SIGN), (WHO), (NIH) and (APA) and additional sources. Three referees independently reviewed articles and selected guidelines for inclusion criteria. Subsequently, 18 trained appraisers independently assessed all 15 guidelines using AGREE II. Results: The mean scores for the six domains and overall quality were computed. More than half of the guidelines (60%) reached the quality threshold with domain scores of 60% for the overall assessment of the guidelines. The overall average quality rating for these guidelines was 58/29%. Conclusion: The applicability of the guidelines needs to be improved in order to improve their relevance and clinical utilization. Families and health care providers play an important role in helping individuals with chronic mental illness throughout the disease course and benefit from pass to well-developed and suitable methods to analyze research knowledge on effective rehabilitation techniques, including the involvement of families in the care